MRI safety management in patients with cardiac implantable electronic devices: Utilizing failure mode and effects analysis for risk optimization. (11th August 2020) - Ryan, James W; Murray, Aoife S; Gilligan, Paddy J; Bisset, James M; Nolan, Chris; Doyle, Audrey; Emerson, Barry; Galvin, Joseph M; Murray, John G
Abstract: Introduction: Cardiac implantable electronic devices (CIEDs) are increasing in prevalence. Exposing patients with CIEDs to magnetic resonance imaging (MRI) can lead to adverse outcomes. This has led certain radiology departments to not accept MRI referrals related to patients with CIEDs. Patients with MR-conditional CIEDs can be safely scanned under specific conditions. Our institution has accepted such referrals since 2014. The aim of this study was to systematically identify and reduce risk in our CIED-MRI protocol using failure mode and effects analysis (FMEA). Methods: A multidisciplinary FMEA team was assembled and included senior stakeholders from the CIED-MRI protocol. A process map was constructed followed by risk analysis and scoring. Targeted interventions were formulated and implemented; high-risk failure modes were prioritized. A new process map and protocol were drafted and repeat risk analysis was performed. Monitoring and re-evaluation of the CIED-MRI pathway were instigated at departmental quality assurance (QA) meetings. Results: Interventions included direct CIED characterization using wireless technology pre-MRI, CIED programming and reprogramming in the MRI suite before and immediately after MRI reducing device downtime and continuous patient monitoring during MRI by a cardiac physiologist. The cumulative risk priority number (RPN) decreased from 1190 pre-FMEA to 492 post-FMEA. Discussion: Despite the risk of exposing CIEDs to the MR environment, patients with MR-conditional CIEDs can be safely scanned with an appropriate multidisciplinary support. We found FMEA an indispensable tool in identifying and minimizing risk with no adverse events recorded since FMEA recommendations were implemented.